THE ROLE OF SYNCHRONOUS TRANSLATION IN LITERARY STUDIES - Nosirova, Dilfuza Mustafoevna; Abdullayeva, Lola Sadullaevna; Qochqorova, Shahodat Ruzievna; Avezova, Nigora Safarovna (International Journal of Psychosocial Rehabilitation, 2020)
Synchronous translation is of great scientific and professional nature, and since it is usually used in official international conferences, synchronous translation requirements are extremely high. Synchronous translation requires that the translator listens and discerns the original language at the time it is spoken, and can quickly predict, comprehend, remember, and direct the original language, relying on thematic knowledge.